Benzene-Poly-Carboxylic Acid Complex, a Novel Anti-Cancer Agent Induces Apoptosis in Human Breast Cancer Cells - Fares, Fuad; Azzam, Naiel; Fares, Basem; Larsen, Stig; Lindkaer-Jensen, Steen (PLOS ONE, 2014)
Some cases of breast cancer are composed of clones of hormonal-independent growing cells, which do not respond to therapy. In the present study, the effect of Benzene-Poly-Carboxylic Acid Complex (BP-C1) on growth of human breast-cancer cells was tested. BP-C1 is a novel anti-cancer complex of benzene-poly-carboxylic acids with a very low concentration of cis-diammineplatinum (II) dichloride. Human breast cancer cells, MCF-7 and T47D, were used. Cell viability was detected by XTT assay and apoptosis was detected by Flow Cytometry and by annexin V/FITC/PI assay. Caspases were detected by western blot analysis and gene expression was measured by using the Applied Biosystems® TaqMan® Array Plates. The results showed that exposure of the cells to BP-C1 for 48 h, significantly (P<0.001) reduced cell viability, induced apoptosis and activated caspase 8 and caspace 9. Moreover, gene expression experiments indicated that BP-C1 increased the expression of pro-apoptotic genes (CASP8AP1, TNFRSF21, NFkB2, FADD, BCL10 and CASP8) and lowered the level of mRNA transcripts of inhibitory apoptotic genes (BCL2L11, BCL2L2 and XIAP. These findings may lead to the development of new therapeutic strategies for treatment of human cancer using BP-C1 analog.